Two Poles on the Use of ICT in Mathematics Education: Opportunities and Challenges - Ghimire , Shree Prasad (Pragyaratna प्रज्ञारत्न, 2024)
This article is a literature-based article exploring the different opportunities and challenges in using ICT. The article examines the use of ICT by categorizing two poles of learning mathematics. This article has explored the fundamental use of ICT in mathematics teaching. The article has also explored what and how different types of ICT tools were used in secondary schools in Nepal, and what challenges arose in learning mathematics with ICT. It is found that numerous opportunities were found for the use of ICT such as the increase in motivation, student engagement, self-paced learning, and maintaining justice in learning mathematics. Similarly, the analysis of different challenges such as cost constraints, knowledge constraints, maintaining equity and access, sustainability, and skilled human resources were found in the use of ICT in classroom instruction.